Gaya Hidup, Literasi, dan Konsumsi: Studi Perilaku Konsumtif Generasi Z Pengguna Shopee PayLater di Kota Padang - Ghani Alghifari; Firman Firman (Pusat Riset dan Inovasi Nasional, 2025)
In light of rising digital consumption trends, this study examines how financial literacy and shopping lifestyle contribute to the consumptive behavior of Generation Z in Padang City, mediated by Shopee PayLater usage. The study involved 150 respondents selected through purposive sampling, consisting of Generation Z individuals residing in Padang who are active users of Shopee PayLater. Primary data were collected through an online questionnaire and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with the assistance of SmartPLS version 4.0. The findings reveal that financial literacy has a positive and significant effect on both consumptive behavior and the use of Shopee PayLater. In addition, the use of Shopee PayLater significantly influences consumptive behavior. Shopping lifestyle also demonstrates a positive and significant impact on both consumptive behavior and the use of Shopee PayLater. However, Shopee PayLater does not significantly mediate the relationship between financial literacy and consumptive behavior. Conversely, it significantly mediates the relationship between shopping lifestyle and consumptive behavior. This study recommends future research to expand the sample size, incorporate additional variables, and adopt a qualitative approach to gain deeper insights into the consumptive behavior of Generation Z.